2017
DOI: 10.1111/jfbc.12433
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective effects ofAsparagus albusleaves in carbon tetrachloride-induced liver injury rats

Abstract: The antioxidant and hepatoprotective activities of hot aqueous extract from Asparagus albus (A. albus) leaf against CCl 4 -induced liver damage in rats were investigated. The total phenolic, flavonoid, and condensed tannin contents of hot aqueous extract from A. albus leaf were determined. The antioxidant activity of hot aqueous extract from A. albus leaf was evaluated using the antioxidant capacity, DPPH free radical-scavenging ability and reducing power assays. Different polyphenolic compounds, namely gallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…Our results also indicated that LPO (lipid peroxidation) was reduced in rabbits treated with the extract; which again confirms its role in scavenging reactive oxygen species (ROS). It is possible that these effects may be directly due to the free radical scavenging potential of the phytoconstituents in the ethanolic extract [47]. Collectively, results of the present study demonstrate that the phytoconstituents contained in an ethanolic extract of Prosopis cineraria pods inhibits HMG -CoA reductase activity and reduces the level of atherosclerotic plaque in hypercholesterolemic rabbits.…”
Section: Discussionmentioning
confidence: 49%
“…Our results also indicated that LPO (lipid peroxidation) was reduced in rabbits treated with the extract; which again confirms its role in scavenging reactive oxygen species (ROS). It is possible that these effects may be directly due to the free radical scavenging potential of the phytoconstituents in the ethanolic extract [47]. Collectively, results of the present study demonstrate that the phytoconstituents contained in an ethanolic extract of Prosopis cineraria pods inhibits HMG -CoA reductase activity and reduces the level of atherosclerotic plaque in hypercholesterolemic rabbits.…”
Section: Discussionmentioning
confidence: 49%
“…Overdose APAP overwhelms the hepatic detoxification process and depletes GSH, which leads to oxidative stress and further contributes to liver injury [28]. Therefore, antioxidants and antioxidant-rich plant may be used as therapeutic agents for liver damage [27, 29, 30]. An increasing body of evidences have proved that alleviating oxidative stress and inflammation would be a potential way to attenuate acute liver injury induced by APAP [3133].…”
Section: Introductionmentioning
confidence: 99%
“…The filtrate is combined, centrifuged at 4000 rpm for 20 min, the supernatant is concentrated to dryness using a rotary evaporator and the residue is stored at 4 ° C until use. This procedure was repeated weekly throughout the study 22 .…”
Section: Preparation Of Curcuma Longa Aqueous Extract (Ce)mentioning
confidence: 99%